Fungos micorrízicos como potencial bioindicador de qualidade do solo de hortas urbanas - Lucas, Vitor Amaral Sanches (Universidade Federal de São Carlos, 2023)
Organic urban agriculture contributes to the population’s food security. Plowing and harrowing are those techniques most used by urban family farmers to prepare soil for planting crops of interest. However, this type of management can interfere with the physical-chemical and biological characteristics of the soil, contributing to reduce the production. In this research, the use of AMF as a bioindicator in evaluating the impact of soil disturbance in urban gardens was proposed. AMF spores were captured in the field and extracted from four plots, two from fallow soils under low solar incidence (FSL) and high solar incidence (FSH) and two from disturbed soils under high solar incidence (DSH) and low solar incidence (DSL). They were evaluated for their AMF density and diversity, their infection potential (Mycorrhizal Colonization) in trap cultivation using Brachiaria decumbens, in addition to the Easily Extractable Glomalin-Related Soil Protein (EE-GRSP). The AMF species were variations in ecological form in terms of distribution of occurrence, through Frequency of Occurrence (FO) and Corrected Global Frequency Index (C-GFI), survival strategy (Competitor, Stress Tolerant and Resistant) and sporulation level through Relative Frequency (FR), in addition to alpha diversity (Specific Diversity, Margalef Index and Shannon-Wiener Index) and beta diversity (Sorensen Index). All parameters were subjected to five repetitions and the results were compared using ANOVA – Tukey 5%. The results demonstrated that the conventional management technique (disturbed) increased spore density in DSL and did not change in FSL, FSH and DSH. CM decreased in DSH and did not change in FSL, FSH and DSL and the EE-GRSP content was higher in disturbed soils (DSH and DSL). Alpha diversity (Shannon-Weaner Index) decreased in FSL and DSL and was maintained in FSH and DSH, but with different species. 39 species of AMF were found with 13 dominant, 13 very common, 10 common and 3 rare species. Finally, glomalin, spore density and AMF species diversity, were viable tools in study of the physical-chemical and microbiological quality of the soil after the impact of applying the tillage management technique in an urban organic garden.
Mycorrhizal fungi as a pontencial bioindicator of soil quality in urban garden
Keywords: Agroecologia; Aração; Densidade de esporos; Diversidade micorrízica; Agroecology; Plowing; Spore density; Mycorrhizal diversity; CIENCIAS BIOLOGICAS::MICROBIOLOGIA::BIOLOGIA E FISIOLOGIA DOS MICROORGANISMOS::MICOLOGIA; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO::MANEJO E CONSERVACAO DO SOLO; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO::MICROBIOLOGIA E BIOQUIMICA DO SOLO; CIENCIAS AGRARIAS; CIENCIAS BIOLOGICAS::BIOLOGIA GERAL; CIENCIAS BIOLOGICAS::ECOLOGIA; CIENCIAS BIOLOGICAS::MICROBIOLOGIA; CIENCIAS BIOLOGICAS; CIENCIAS BIOLOGICAS::ECOLOGIA::ECOLOGIA APLICADA; CIENCIAS BIOLOGICAS::ECOLOGIA::ECOLOGIA DE ECOSSISTEMAS; CIENCIAS AGRARIAS::AGRONOMIA::FITOSSANIDADE::MICROBIOLOGIA AGRICOLA; CIENCIAS BIOLOGICAS::MICROBIOLOGIA::MICROBIOLOGIA APLICADA; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO RURAL